Dinámica del comportamiento fractal de las estructuras a gran escala del cosmos (2009)
In this review article the most important foundations of fractal cosmology are presented. Special attention is given to the first theoretical developments in gravitational dynamics based on the conditional cosmological principle proposed by Mandelbrot and to the starting research about the fractal nature of the observed spatial clustering of galaxies. The understanding of this phenomena may impulse the development of new physics beyond the standard cosmological model.